Enhancing ICT Competencies of Madrasah Ibtidaiyah Teachers through TPACK-Based Coaching in Digital Learning Media Development in Cirebon City - Syibli Maufur; Ahmad Arifuddin; Dadan Setiawan (Indonesian Journal of Elementary Education (IJEE), 2024)
This study aims to analyze the effectiveness of TPACK-based coaching in improving ICT competencies of Madrasah Ibtidaiyah teachers in Cirebon City. Employing a one-group pretest-posttest design, the research involved 25 MI teachers selected through purposive sampling and conducted in October 2023. The one-month intensive coaching program integrated group workshops (8 hours) and individual mentoring (8 hours) focusing on digital learning media development. Data were collected through the TPACK Survey Instrument (42 items, α = 0.89) and Digital Media Quality Assessment Rubric. Paired-samples t-test analysis revealed significant improvements across all TPACK domains (p < .001), with the largest effect sizes in Technological Knowledge (d = 3.26) and TPACK (d = 3.12). Teachers' TPACK competencies increased from low category (M = 2.48, SD = 0.55) to high category (M = 3.97, SD = 0.39). All participants successfully developed good-quality digital learning media (M = 3.22, SD = 0.48), with diverse media types including interactive video learning (32%), multimedia presentations (24%), and educational games (20%). Findings confirm that TPACK-based coaching model effectively enhances madrasah teachers' ICT competencies and abilities to develop pedagogically sound and contextual digital learning media. This study contributes a theoretical TPACK coaching model for madrasah contexts and practical recommendations for sustainable MI teacher professional development